1999
DOI: 10.1007/bf02433824
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant probucol as an effective scavenger of lipid radicals in low density lipoproteinsin vivo andin vitro

Abstract: Probucol in concentrations of 10-50/aM effectively inhibits CuZ+-induced free radical oxidation of native low density lipoproteins and in concentration of 100 ~tM it inhibits lipoperoxide formation. The mean plasma concentration of probucol in patients receiving 250 mg of this drug is 25 ~tM. Both 250 and 1000 mg probucol daily during 3-6 month block the oxidation of isolated low density lipoproteins. Electron paramagnetic resonance spectrometry data showed that probucol incorporated in vivo into lipoprotein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…At the same time, it has been shown that administration of α-TOH at high doses has no effect on LDL oxidizability in CHD patients in vivo [ 101 ]. Thus, it should be recognized that the use of α-TOH to inhibit LDL oxidizability in clinical trials is not justified and the use of coenzyme Q [ 6 , 100 ] and other phenolic antioxidants, in particular probucol [ 6 , 101 , 108 , 109 , 110 ], whose effectiveness in inhibiting LDL oxidation is convincingly confirmed, is more correctly for LDL protection against oxidation [ 6 , 101 ]. It is also clear that it is unacceptable to use data about the “negative” results obtained with individual antioxidants, such as α-TOH and β-carotene [ 92 , 93 , 94 ], for the entire group of antioxidants [ 80 ], which includes a large number of substances with very different structures and mechanisms of action.…”
Section: Antioxidants In Cardiology: Pro Et Contramentioning
confidence: 99%
“…At the same time, it has been shown that administration of α-TOH at high doses has no effect on LDL oxidizability in CHD patients in vivo [ 101 ]. Thus, it should be recognized that the use of α-TOH to inhibit LDL oxidizability in clinical trials is not justified and the use of coenzyme Q [ 6 , 100 ] and other phenolic antioxidants, in particular probucol [ 6 , 101 , 108 , 109 , 110 ], whose effectiveness in inhibiting LDL oxidation is convincingly confirmed, is more correctly for LDL protection against oxidation [ 6 , 101 ]. It is also clear that it is unacceptable to use data about the “negative” results obtained with individual antioxidants, such as α-TOH and β-carotene [ 92 , 93 , 94 ], for the entire group of antioxidants [ 80 ], which includes a large number of substances with very different structures and mechanisms of action.…”
Section: Antioxidants In Cardiology: Pro Et Contramentioning
confidence: 99%
“…The protection from the atherosclerosis and the treatment of the disease are complex problems with many unknowns, and so are the modes of action of novel drugs and their metabolism. Many studies concerning probucol and succinobucol have been published [ 13 , 14 , 15 , 20 , 21 , 22 , 23 ]. Starting with these conjugates, a long pathway to discover their real potential is ahead.…”
Section: Introductionmentioning
confidence: 99%